Découverte d’un rempart antérieur à la tour maîtresse du château de Loches (Indre-et-Loire) : la question du système défensif originel - Pierre Papin (Revue Archéologique du Centre de la France)
In 2015, as part of an archaeological diagnosis on the ground floor of the donjon of the castle of Loches (Indre-et-Loire), two surveys were carried out inside the famous monument. These partially uncovered an imposing structure formed by a earthen slope clad with dry stones. This discovery makes it possible to call into question the old theory of a castral motte which would have been earlier of the building of the stone tower and to propose a new hypothesis: that of a large rampart preceded by a ditch barring the rocky outcrop, above which the donjon was built during the first third of the 11th century. However, the dating of this work remains poorly defined, but some arguments allow to suppose that it was erected during the second half of the 10th century.